Introduction: conceptualizing hubs of illicit trade - Krylova, Yulia (Hubs of illicit trade in the global economy, 2025)
Chapter 1 describes the objective of the volume, explains its terminology, and presents a methodology of the research. It provides a general framework for analyzing various hubs of illicit trade worldwide that goes beyond a traditional focus on organized crime and state actors and includes a wide range of legitimate companies and enablers engaged in illicit trade. It offers a multi-dimensional approach for cross-hub comparisons and measuring the scale of their illicit activities based the assessment of illicit trade risk levels that combines indicators related to all aspects of illicit trade, including corruption in the private and public sectors, money laundering, and financial secrecy, among other dimensions. This chapter also provides multiple perspectives on illicit trade drivers and enablers at the country and regional levels.